Implementasi Pancasila dalam Kebijakan Ekonomi di Indonesia - Hamid, Abd (Idarotuna : Journal of Administrative Science, 2024)
The purpose of this study is to examine how Indonesian economic policy incorporates Pancasila values. Pancasila, the state's fundamental ideology, serves as a framework for the development of governmental policies, including those pertaining to the economy. It is anticipated that pancasila values—such as economic sovereignty, shared prosperity, and social justice—will serve as the foundation for the development of people-supporting policies. However, in reality, neoliberal economic policies, globalization, and international market forces frequently pose obstacles to the adoption of Pancasila ideals. This study examines Indonesia's economic policies at the national and regional levels using qualitative methods and a descriptive-analytical approach. It also assesses how well Pancasila values have been incorporated. The fourth and fifth Pancasila principles are reflected in this study's explanation of the government's responsibility in formulating policies based on people's economic circumstances. The study's findings indicate that while a number of economic measures, including initiatives to reduce poverty and promote equitable economic growth, have attempted to apply Pancasila values, there is a disconnect between the ideals of Pancasila and their practical application. Therefore, in order to strike a balance between economic growth and equitable social welfare distribution, more work is required to improve the integration of Pancasila ideals and economic policies.